2023
DOI: 10.3390/molecules28052279
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Composition and Antimicrobial Activity of Essential Oil from the Leaves of Artemisia vulgaris L.

Abstract: Artemisia vulgaris is an enormously useful aromatic plant known for its insecticidal, antifungal, parasiticidal, and medicinal values. The main aim of this study is to investigate phytochemical contents and the potential antimicrobial activities of Artemisia vulgaris essential oil (AVEO) from the fresh leaves of A. vulgaris grown in Manipur. The AVEO isolated by hydro-distillation from A. vulgaris were analyzed by gas chromatography/mass spectrometry and solid-phase microextraction-GC/MS to describe their vola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…To find and ascertain the antibacterial activity of essential oils, recently, numerous studies have been carried out [ 50 ]. Although the exact mechanism of action is still unknown, several investigations have indicated that essential oil components may enter cells and disrupt cellular metabolism [ 51 ]. Phenols, such as eugenol and carvacrol, damage cellular membranes and interact with enzyme-active sites.…”
Section: Discussionmentioning
confidence: 99%
“…To find and ascertain the antibacterial activity of essential oils, recently, numerous studies have been carried out [ 50 ]. Although the exact mechanism of action is still unknown, several investigations have indicated that essential oil components may enter cells and disrupt cellular metabolism [ 51 ]. Phenols, such as eugenol and carvacrol, damage cellular membranes and interact with enzyme-active sites.…”
Section: Discussionmentioning
confidence: 99%
“…The main constituents of Zanthoxylum bungeanum essential oil, extracted using a low-eutectic solvent and steam distillation, were terpineol-4-ol (13.13%) and (–)-β-pinene (11.17%) [ 51 ]. Many studies have shown that differences in the prominent essential oil compounds could be explained by variables such as harvest time, plant ontogeny, geographical location, plant parts, as well as extraction techniques [ 52 , 53 , 54 , 55 , 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…The GC-MS employed have Trace1300 as Gas chromatography and TSQ DUO as Mass Spectrophotometry. The GC have the silica capillary column (30 m X 0.25 mm; 0.25 µm film thickness), TG-5 MS interfaced with the MS.The carrier gas used in the instrument was helium with a flow rate of 1 ml/min for 60 minutes [ 18 , 19 ]. The ionization energy was set at 70 eV, and the mass transfer line temperature at 250°C and the ion source temperature at 280°C.…”
Section: Methodsmentioning
confidence: 99%
“…The ionization energy was set at 70 eV, and the mass transfer line temperature at 250°C and the ion source temperature at 280°C. The column temperature was programmed from 40°C for 1 min to 280°C at the rate of 5°C/min by a heating ramp for 20 min and held at 250°C.The inlet injector temperature was set at 240°C with a split mode of 1:20 maintained [ 18 , 19 ]. The mass spectra were filtered from the mass range from 35 to 450 Mw.The identification of the volatile compound was determined by comparing the spectra obtained from the sample with the reference to the mass spectrum given by the National Institute of Standards and Technology (NIST) GC/MS Libraries 2017 [ 19 ].…”
Section: Methodsmentioning
confidence: 99%